EVALUATION OF TOXICITY OF SOME INDUSTRIAL EFFLUENTS TO FISH BY BIO-ASSAYS - Ray, P (Indian Journal of Fisheries, 2011)
DETERMINATION of minimal lethal doses of industrial effluents which killtest animals in a particular period, is necessary in setting up standards forsafe disposal of such wastes. Keeping in view the quality of water in theriver, its volxmie, flow and the nature of soil in the river-bed, such standardscan greatly help in conserving fish populations in our rivers. It is only withthe help of bio-assay experiments, that toxicity limits of any pollutant substancein an effluent can be estabUshed by evaluating the median tolerancelimit or " TLm " for the particular waste which being diluted in water to aknown extent, causes 50 per cent, mortality of the test fish in a specified time.The TLm values are thus obtained by straight line interpolation from pointsrepresenting per cent survival of fish and log concentrations of materialin question which bracket the 50 per cent survival point (Henderson andTarzwell, 1957).